Clinical Presentation of Children With Gastroschisis and Small for Gestational Age - I-Lun Chen; Shin-Yi Lee; Mei-Chen Ou-Yang; Pei-Hsin Chao; Chieh-An Liu; Feng-Shun Chen; Mei-Yung Chung; Chih-Cheng Chen; Hsin-Chun Huang (Pediatrics and Neonatology)
Gastroschisis (GS) is defined as a full-thickness paraumbilical abdominal wall defect associated with evisceration of fetal abdominal organ. Although the concomitant nongastrointestinal anomalies and aneuploidy are rarely presented, fetal growth restriction is common. The aim of this study is to compare the primary and secondary outcomes of GS between infants small for gestational age (SGA) and those appropriate for gestational age as well as term and late preterm infants. Methods: Chart records of neonates born with gestational age at or more than 34 weeks were reviewed. All babies received repair procedure immediately after birth. SGA was defined as birth weight for gestational age below the 10th percentile. The primary outcomes were the length of hospital stay, duration of total parental nutrition used, and the surgical complications. The secondary outcome was the percentile of body weight at 6 months old. Results: There were 21 babies diagnosed with GS from January 1990 to January 2010 at Kaohsiung Chang Gung Memorial Hospital. Four (19%) babies expired soon after operation. Nine (53%) of the 17 surviving babies had SGA. Length of hospital stay, surgical complications, and the percentile of body weight at 6 months old were significantly poorer for the SGA compared with appropriate for gestational age group (p = 0.005, 0.050, and 0.035). Furthermore, preterm neonates in SGA group had lower Apgar scores at 1 minute and 5 minutes than did term neonates (p = 0.045 and 0.031). Conclusion: SGA commonly occurred in GS cases and it was associated with longer hospital stay, more operative complications, and less body weight gain. Our conclusion may provide informative data to parents of GS fetuses during prenatal consultation, and reminds us that long-term follow-up of these cases could be necessary.